Prognostic markers compared to CD3+TIL in locally advanced nasopharyngeal carcinoma. Issue 46 (19th November 2021) - Al-Rajhi, Nasser; Mohammed, Shamayel F.; Khoja, Hatim A.; Al-Dehaim, Mohammad; Ghebeh, Hazem
Abstract : Abstract: Locally advanced nasopharyngeal carcinoma (LA-NPC) is more prevalent in some geographic regions, including Saudi Arabia. Typically, Tumor-Node-Metastasis (TNM) staging is used in NPC. However, it is inadequate to assess the prognosis of LA-NPC. Therefore, we analyzed and compared several previously reported prognostic factors in LA-NPC patients, retrospectively, including CD3+tumor-infiltrating lymphocytes (TIL) and peripheral blood hemoglobin, EBV DNA copy number, ratios of albumin-to-alkaline phosphatase ratio (AAPR), neutrophils, or platelets-to-lymphocytes (NLR, PLR). The studied cohort was 83 LA-NPC patients previously recruited for a randomized phase II trial with a different aim. Univariate cox regression analysis showed no significant correlation between any of the tested variables with disease-free survival (DFS) or overall survival (OS) with the exception of low CD3+ TIL infiltration, which correlated significantly with DFS (HR = 6.7, P = <.001) and OS (HR = 9.1, P = .043). Similarly, in a validated multivariate cox regression analysis, only low CD3+ TIL correlated significantly with DFS (HR = 7.0, P < .001 for TIL) and OS (HR = 9.4, P = .040). Among tested parameters, CD3+ TIL was the only independent prognostic marker for DFS and OS in LA-NPC patients treated with CCRT. This study supports the use of CD3+TIL, over other factors, as an independent prognostic factor in LA-NPC.